Fourier descriptors under rotation, scaling, translation and various distortion for hand drawn planar curves - Saxena, Vinay (Journal of Experimental Sciences, 2012)
The ordinary Fourier coefficients are difficult to use as input to categorizers because they contain factors dependent upon size and rotation as well as an arbitrary phase angle. From these Fourier coefficients, however, other more useful features are derived. By using these derived property constants, a distinction is made between genuine shape constants and constants representing size, location and orientation. In the present work, we extended the method of Fourier descriptors to produce a set of normalized coefficients, which are invariant under RST (Rotation, Scaling and Translation) for hand drawn planar curves. We have used these shapes for study of the behavior of Fourier descriptors under various distortions. For such planar curves, the optimal curve matching technique is used.